ANALYZING THE IMPACT OF CORPORATE DECISION WITHIN MULYONO’S BRAND COMMUNITY - Syailendra, Alif Aviano; Hudrasyah, Herry (Journal of Business and Management, 2017)
Abstract. Mulyono is a Community based event organizing brand that is currently struggling to survive due to the fact that it is lacking any sort of income, but making a decision in Mulyono is not that simple, since it is known by the Brand Community (as their main customers) as a deeply independent brand. This research evaluates the performance of Mulyono’s events through its community while validating prospects of income, using descriptive analysis based on the 7P of marketing mix (Booms, Bernard, and Mary Jo, 1981) survey that is analyzed using frequency, factor and Logistic regression analysis. The results from this research shows that there is no significant influence towards the decision based on the regression model. And successfully maps its model of likely influence that suggests Publication is the most prominent factor that influences Customer satisfaction while Logistic is the opposite. Keywords : Counterculture Carnivalesque, Music Festivals, Event Organizing, Community Brand, Brand Community